THE EFFECTIVENESS OF USING AUTHENTIC MATERIALS IN TEACHING DESCRIPTIVETEXT TOWARD WRITINGABILITY - Ilham Ilham (Linguistics and ELT Journal, 2015)
This research is intended to find out the effectiveness of using authentic materials in teaching descriptive text toward students’ writing ability. This study was conducted in MTs. Nurul Jannah NW Ampenan.There were two classes of eighth-grade students with each class were 20 students. So, the total numbers of students in the eighth grade of MTs Nurul Jannah NW Ampenan were 40 students. The writer took class A as experiment group and class B as a control group. The experimental group was treated by using authentic materials and the control group was treated without authentic materials. Before giving instructions, two groups were given pre-test. After that, they were given post-test. The result showed that the mean score of the experimental group was 28 and the mean score of control group 7,25. The standard deviation of the experimental group was 2363 and the standard deviation of the control group was 173,75. The final result obtained through analysis of the data was the value of t-test 8,042. This consulted to the value of t-table which was 2,750< (8,042>2,750). It indicated that the value of t-test was higher than the value of t-table. It meant that an authentic material was effective in teaching descriptive text toward students’ writing ability.